Nano-Based Drug Delivery Systems: Potential Developments in the Therapy of Metastatic Osteosarcoma—A Narrative Review - Yuanrui Luo; Minghao Sun; Linyun Tan; Tao Li; Li Min (Pharmaceutics, 2023)
Osteosarcoma, a predominant malignant bone tumor, poses significant challenges due to its high metastatic and recurrent nature. Although various therapeutic strategies are currently in use, they often inadequately target osteosarcoma metastasis. This review focuses on the potential of nanoscale drug delivery systems to bridge this clinical gap. It begins with an overview of the molecular mechanisms underlying metastatic osteosarcoma, highlighting the limitations of existing treatments. The review then transitions to an in-depth examination of nanoscale drug delivery technologies, emphasizing their potential to enhance drug bioavailability and reduce systemic toxicity. Central to this review is a discussion of recent advancements in utilizing nanotechnology for the potential intervention of metastatic osteosarcoma, with a critical analysis of several preclinical studies. This review aims to provide insights into the potential applications of nanotechnology in metastatic osteosarcoma therapy, setting the stage for future clinical breakthroughs and innovative cancer treatments.